Autopoiesis, intracrinology, and the self: toward a new model of mental health - Susan Gordon (Academia Mental Health & Well-Being)
New models of mental health are needed to move us beyond psychopathology and biological reductionism, toward an understanding of the phenomenological structures of consciousness and the experienced world—selfhood, temporality, spatiality, affectivity, and embodiment—in relation to biological processes, using an enactive, interdisciplinary framework for explaining the human condition. This review article applies these concepts to the psychoneurointracrine model and the emerging role of the intracrine biosynthesis of dehydroepiandrosterone (DHEA), progesterone (PG), and neurosteroids in peripheral intracellular metabolism impacting the responsiveness of the HPA axis and the sense of well-being. More than three quarters of the hormonal activity of androgens and estrogens in humans is created intracrinologically within peripheral tissue through de novo biosynthesis within the cytoplasm of cells. Intracrine biosynthesis is evolutionary and also autopoietic in the sense that the person’s perception of experience determines the sensitivity of hormone receptors subserving homeostatic and psychoemotional needs. Hormone balance is integral to embodied self-awareness, the development of meaning, and the integration of personality, which are managed autopoietically through the intracrine biosynthesis of sex and adrenal steroids. This review concludes with a discussion of the implications of this model for mental health and well-being that are of value to psychiatric research and clinical practice.